IMPLEMENTATION OF CRISIS MANAGEMENT BY KMI TRUBUS IMAN PUBLIC RELATIONS IN FACING PUBLIC ISSUES - Syahputra, Anggi; Al Anshori, Habib Anwar; Fajri, Muhamad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Public Relations (PR) plays a strategic role in maintaining and enhancing the image of an institution, especially in crisis situations that can affect public trust. This study aims to analyze the crisis management implementation by the PR team of KMI Trubus Iman in addressing public issues that have the potential to harm the institution's reputation. The research focuses on the strategies applied, the challenges faced, and the impact of crisis management on public image and trust.This research uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with the PR team, direct observation, and documentation related to the PR activities of KMI Trubus Iman. Data analysis was performed thematically to identify patterns and key findings. The results indicate that the PR team of KMI Trubus Iman has implemented several crisis management strategies, such as transparent communication management, the use of social media as a mitigation tool, and collaboration with community leaders in restoring the institution’s image. However, there were several challenges, including a lack of competent human resources in the PR field, budget limitations, and challenges in handling the rapid spread of negative information in the digital era. Despite these challenges, the PR team's efforts were deemed effective in maintaining public trust in KMI Trubus Iman, as evidenced by the increased community participation in post-crisis school programs. This study concludes that effective crisis management implementation requires careful planning, strengthening human resource capacity, and utilizing information technology. Recommendations are made to improve the effectiveness of PR at KMI Trubus Iman, including specialized training in crisis management and the development of a digital issue monitoring system. The findings of this research are expected to serve as a reference for other educational institutions in managing crises and building public trust